Estimated 24-hour urinary sodium excretion and incident cardiovascular disease and mortality among 398 628 individuals in UK biobank. - Elliott,P; Muller,DC; Schneider-Luftman,D; Pazoki,R; Evangelou,E; Dehghan,A; Neal,B; Tzoulaki,I (Hypertension, 2020)
We report on an analysis to explore the association between estimated 24-hour urinary sodium excretion (surrogate for sodium intake) and incident cardiovascular disease (CVD) and mortality. Data were obtained from 398 628 UK Biobank prospective cohort study participants (40-69 years) recruited between 2006 and 2010, with no history of CVD, renal disease, diabetes mellitus or cancer, and cardiovascular events and mortality recorded during follow-up. Hazard ratios between 24-hour sodium excretion were estimated from spot urinary sodium concentrations across incident CVD and its components and all-cause and cause-specific mortality. In restricted cubic splines analyses, there was little evidence for an association between estimated 24-hour sodium excretion and CVD, coronary heart disease, or stroke; hazard ratios for CVD (95% CIs) for the 15th and 85th percentiles (2.5 and 4.2 g/day, respectively) compared with the 50th percentile of estimated sodium excretion (3.2 g/day) were 1.05 (1.01-1.10) and 0.96 (0.92-1.00), respectively. An inverse association was observed with heart failure, but that was no longer apparent in sensitivity analysis. A J-shaped association was observed between estimated sodium excretion and mortality. Our findings do not support a J-shaped association of estimated sodium excretion with CVD, although such an association was apparent for all-cause and cause-specific mortality across a wide range of diseases. Reasons for these differences are unclear; methodological limitations, including the use of estimating equations based on spot urinary data, need to be considered in interpreting our findings.